Simplified computer programs for search of homology within nucleotide sequences. - Kröger, M (1984)
Four new computer programs for search of homology within nucleotide sequences are presented. The main scope of the program design is flexibility, independence of sequence length and the capability to be used by any molecular biologist without any prior computer experience. The programs offer a linear search, a search for maximal identity, an alignment along a given sequence and a search based on homology within the amino acid coding capacity of nucleotide sequences. The language is Fortran V. Copies are available on request.